Functional Pearl: La Tour D'Hanoï - Hinze, R (2009)
This pearl aims to demonstrate the ideas of wholemeal and projective programming using the Towers of Hanoi puzzle as a running example. The puzzle has its own beauty, which we hope to expose along the way. © 2009 ACM.